2004
DOI: 10.1007/s00425-004-1287-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a deregulated tobacco nitrate reductase gene in potato increases biomass production and decreases nitrate concentration in all organs

Abstract: We investigated the physiological consequences for nitrogen metabolism and growth of the deregulated expression of an N-terminal-deleted tobacco nitrate reductase in two lines of potato (Solanum tuberosum L. cv Safrane). The transgenic plants showed a higher biomass accumulation, especially in tubers, but a constant nitrogen content per plant. This implies that the transformed lines had a reduced nitrogen concentration per unit of dry weight. A severe reduction in nitrate concentrations was also observed in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Moreover, we noted two interesting features of this cultivar: -relatively high activity of nitrate reductase at two final harvests (142 and 178 DAS) in comparison to earlier phases, and -high concentration of total chlorophyll during the whole growing season (particularly in the plants emerged from both energ'hill seeds and seeds treated by laser D5). Djennane et al (2004) stated that the enhancement of the nitrate reduction rate may lead to higher biomass production. Chen et al (2005b) showed that laser pretreatment induces statistically significant changes in some biochemical and physiological parameters in seedlings of Isatis indogotica.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we noted two interesting features of this cultivar: -relatively high activity of nitrate reductase at two final harvests (142 and 178 DAS) in comparison to earlier phases, and -high concentration of total chlorophyll during the whole growing season (particularly in the plants emerged from both energ'hill seeds and seeds treated by laser D5). Djennane et al (2004) stated that the enhancement of the nitrate reduction rate may lead to higher biomass production. Chen et al (2005b) showed that laser pretreatment induces statistically significant changes in some biochemical and physiological parameters in seedlings of Isatis indogotica.…”
Section: Resultsmentioning
confidence: 99%
“…The higher nitrate content in the HNR genotype might be due to its better nitrate uptake capacity. It is also noteworthy that the HNR genotype produced more than twice as much biomass as the LNR genotype possibly because of its higher nitrate Downloaded by [University of Saskatchewan Library] at 11:12 19 November 2014 reduction rate, thus allowing a better allocation of nitrogen resources to photosynthesis and carbon metabolism (Djennane et al, 2004). These findings are in consonance with the view that the plant's capacity for biomass production and nitrogen uptake may be highly dependent on environmental conditions including the nitrate supply (Lawlor, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…In another variety of potato, the transgenic plants showed a marked improvement in biomass production, especially in tubers, with still lower amounts of nitrate. The more effective reduction of nitrate probably allowed a better allocation of N to the photosynthetic apparatus and to enzymes involved in C metabolism, which was demonstrated by higher leaf chlorophyll content in the transgenic potato plants [173].…”
Section: Improvement Of Nitrogen Utilization Using Genetically Modifimentioning
confidence: 99%